PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS III SD NEGERI 188 PEKANBARU - Iggo Mayyudin Nugroho (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This research was motivated by the low learning outcomes of third-grade Civics (PKn) students at SD Negeri 188 Pekanbaru, with a class average score of 68.25. Of the 40 students, only 17 achieved the minimum mastery criteria. This study employed classroom action research aimed at improving the Civics learning outcomes of third-grade students at SD Negeri 188 Pekanbaru through the application of the Make a Match type cooperative learning model. The subjects of this study were third-grade students of SD Negeri 188 Pekanbaru in the 2018/2019 academic year. Data were collected using teacher activity observation sheets, student activity observation sheets, and learning outcome tests. The results showed that the average learning outcome increased from 68.25 before the action to 76.87 in Cycle I, representing an improvement of 12.63%. In Cycle II, the average score further increased to 81.50, indicating an improvement of 19.41%. Teacher activity also improved, with a percentage of 62.50% (sufficient category) at the first meeting of Cycle I, increasing to 79.16% (good category) at the second meeting. In Cycle II, teacher activity increased to 83.33% (good category) at the first meeting and reached 95.83% (very good category) at the second meeting. These findings indicate that students demonstrated better understanding of Civics learning after the implementation of the Make a Match cooperative learning model, as reflected in increased teacher activity, student activity, and learning outcomes in each cycle. The study concludes that the Make a Match cooperative learning model effectively improves Civics learning outcomes of third-grade students at SD Negeri 188 Pekanbaru.